Pengujian Cost Agent terhadap Kinerja Keuangan - Suharyanto; Sumaryo (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To examine the effect of solvability on financial performance and agency costs moderating the effect of solvency on financial performance in a developing country, Indonesia. Background Problems: Does agency costs moderate the relationship that affects solvabilty on financial performance. Novelty: The Cost Agency (CA) aspect is one of the important keys to CG and an entry point for Stakeholders in mining companies in Indonesia, because there is little information on CA. Research Method: Data is collected from financial reports published on the Indonesia Stock Exchange, company performance is measured using data accounting and market indicators, agency costs are measured by the ratio of operational costs to total sales, testing for SPSS applications and purposive sampling methods are used for data analysis. Finding/Results: Stakeholder theory in explaining the influence of solvency on financial performance. Agency fees have a considerable influence on solvency on company performance, namely agency fees moderate the relationship between solvency and financial performance. Conclusion: These results are key evidence from a developing country, Indonesia to support the stakeholder theory argument which provides significant insights for managers in the mining sector.